Legal Certainty and the Suspension of Criminal Investigations Due to Civil Disputes in Indonesian Criminal Law Practice - Junaedi, Nurhadi; Siradjz, Derex Anoraga; Prayuti, Yuyut (Research Horizon, 2025)
Criminal and civil law often intersect in land ownership disputes, particularly when land grabbing cases are delayed due to ongoing civil litigation. This creates challenges in law enforcement, especially regarding legal certainty, justice, and utility. This study aims to examine how legal protection is provided to complainants in criminal cases involving sufficient evidence under Article 184 of the Criminal Procedure Code, when the investigation is suspended due to civil disputes. It also investigates whether the suspension practice based on the Chief of Police’s Telegram Letter, referring to Supreme Court Regulation (Perma) Number 1 of 1956, aligns with the principles of legal certainty and justice. The study adopts a normative juridical approach, using statutory, theoretical, and case-based analysis. It focuses on in-concreto legal evaluation, especially on whether criminal investigations should proceed or be postponed pending civil decisions. Findings show that although Perma Number 11956 provides procedural guidance for prejudicial disputes, its application often leads to legal uncertainty and risks case expiration. This creates dualism in judicial practice. Law enforcement authorities must carefully assess the status of civil claims before halting criminal investigations. Future research should address the need for more integrated regulations to avoid conflicting practices between civil and criminal proceedings.